Β‑aminoisobutyric acid ameliorates hypertensive vascular remodeling via activating the AMPK/SIRT1 pathway in VSMCs. Issue 6 (1st June 2022) - Yin, Bo; Wang, Yu-Bin; Li, Xiang; Hou, Xu-Wei
ABSTRACT: Excessive proliferation and migration of vascular smooth muscle cells (VSMCs) play a fundamental role in the pathogenesis of hypertension-related vascular remodeling. β-aminoisobutyric acid (BAIBA) is a nonprotein β-amino acid with multiple pharmacological actions. Recently, BAIBA has been shown to attenuate salt‑sensitive hypertension, but the role of BAIBA in hypertension-related vascular remodeling has yet to be fully clarified. This study examined the potential roles and underlying mechanisms of BAIBA in VSMC proliferation and migration induced by hypertension. Primary VSMCs were cultured from the aortas of Wistar-Kyoto rats (WKY) and spontaneously hypertensive rats (SHR). Our results showed that BAIBA pretreatment obviously alleviated the phenotypic transformation, proliferation, and migration of SHR-derived VSMCs. Exogenous BAIBA significantly inhibited the release of inflammatory cytokines by diminishing phosphorylation and nuclear translocation of p65 NFκB, retarding IκBα phosphorylation and degradation, as well as erasing STAT3 phosphorylation in VSMCs. Supplementation of BAIBA triggered Nrf2 dissociation from Keap1 and inhibited oxidative stress in VSMCs from SHR. Mechanistically, activation of the AMPK/sirtuin 1 (SIRT1) axis was required for BAIBA to cube hypertension-induced VSMC proliferation, migration, oxidative damage and inflammatory response. Most importantly, exogenous BAIBA alleviated hypertension, ameliorated vascular remodeling and fibrosis, abated vascular oxidative burst and inflammation in SHR, an effect that was abolished by deficiency of AMPKα1 and SIRT1. BAIBA might serve as a novel therapeutic agent to prevent vascular remodeling in the context of hypertension. Graphic Abstract: uf0001